Implementing the learning health system paradigm within academic health centers - Douglas Easterling; Anna Perry; David Miller (Wiley, 2024)
Abstract Introduction The learning health system (LHS) concept represents a bold innovation that combines organizational learning, strategic analysis of patient data, stakeholder engagement and the systematic translation of research into practice - all in service of improving the quality of health care delivered across the organization. This innovation has been diffused and widely adopted by healthcare organizations over the past 15 years, but academic health centers (AHCs) have been slower on the uptake. The irony is that AHCs have the resources (e.g., trained researchers, sophisticated clinical data systems, informatics infrastructure) that are necessary to do the highest‐quality and most impactful LHS work. Methods Based on a review of publications describing how AHCs have implemented LHS work, as well as the authors' direct experience promoting the adoption of the LHS paradigm at Atrium Health Wake Forest Baptist (AHWFB), we:identify a set of factors that have inhibited broader adoption of the LHS paradigm among AHCs; distinguish between the forms of LHS work that are consistent and inconsistent with the mission of AHCs; and offer recommendations for broader adoption and fuller implementation of the LHS paradigm. Results The LHS paradigm represents an expansion of the scientific paradigm which serves as the foundation of research enterprise within AHCs. Both paradigms value rigorous studies of new treatments and practices, including pragmatic clinical trials. The LHS paradigm also places a high value on quality improvement studies, organizational learning, and the translation of research findings into improved patient care and operations within the local health system. The two paradigms differ on the origin of the research question, i.e., a pressing patient‐care issue facing the health system versus the investigator's own research interests. Academic researchers have been disincentivized from pursuing at least some forms of LHS research. However, a growing number of AHCs are finding ways to integrate the LHS paradigm into their research enterprise, either by providing research faculty with institutional funding to cover their effort on studies that address the health system's priority issues, or by establishing an institute dedicated to LHS research. Conclusions The LHS paradigm is a disruptive intervention for AHCs, one that was initially resisted but is increasingly being embraced. AHCs are developing strategies for conducting LHS research, typically in parallel to the more traditional biomedical science that is core to academic medicine. Full implementation of the LHS paradigm will require further alignment between LHS and science, including a shift in the criteria for promotion and tenure to support those researchers who choose to focus on the pressing issues facing the health system.